PENENTUAN JARAK GALAKSI DEKAT DENGAN MENGGUNAKAN CEPHEID: KOREKSI TERHADAP POSISI CEPHEID DAN ORIENTASI GALAKSI - Fariz, Ahmad
Distance measurement using Cepheid variables period-luminosity relation can be used to measure distances from order of 1 kpc to 10 Mpc. This method is used as a calibrator to other methods such as Tully-Fisher and type Ia supernovae to measure the distance of objects even further. Cepheid variables period-luminosity relation is the first rung in the cosmological distance ladder. Therefore, a thorough examination for this method is very important. This final project focuses on the effects of Cepheids’ positions in galaxy and galaxy’s orientation. We obtain the position of the Cepheids from the archives of the Hubble Space Telescope Key Project on the Extragalactic Distance Scale and from several papers from the Araucaria Project, while we obtain the inclination of the galaxies from galaxy catalog http://www.sao.ru/lv/lvgdb/. We then develop a system which produces correction that transforms the distance of the Cepheids as a representation of the distance to the center of the galaxy.